Comparative Analysis of E-Learning in Private and Public Sector Medical and Dental Institutes in Pakistan - Zainab Tasadaq Cheema, Hammad Hassan, Shanzay Bilal Kayani, Talha Aslam, Salman Aziz, Asma Tasadaq Cheema, Muhammad Saad Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study was to analyze the public and private sector medical and dental institutions’ management of online education amidst the COVID-19 pandemic in Pakistan and to understand whether their respective modes derived satisfaction of e-learning from students. Methods: We conducted a survey of 371 students of various public and private sector medical and dental institutions across Pakistan, investigating their experience, confidence, and satisfaction regarding e-learning. The survey was carried out using ‘Google Forms’, which was sent via email to students. Results: In total, 371 responses were received. Despite the differences in resources and facilities, students of both sectors had not been confident in taking professional exams after the shift to online education: public (81.3%) and private (74.4%); very few students felt confident about their knowledge of basic medical sciences without labs/ practical work: public (10.8%) and private (10.3%); and more than 80% from both sectors also held the belief that e-learning is not sufficient to support academics. Conclusion: Private medical and dental institutes in Pakistan have better funding but students still felt under-confident. Public sector institutes lacked a developed IT department and had an irregular and erratic schedule of online lectures with limited engagement from professors. Many felt that online and traditional learning can be blended to bring forth a form of learning known as "blended learning". Keywords: Blended Learning; E-Learning; Medical Education; Pandemic.